Tinjauan Usaha Berdasar Analisa Laporan Rugi Laba Sebagai Acuan Pengambilan Keputusan Strategis - Arief Saptono (UNIVERSITAS RAHARJA, 2017)
Business activity with profit orientation required standard to measure its success. Store Operational Income is used as a critical success indicator in Outlet Burger King, a positive SOI on the Profit and Lost Statement (P & L) report means our business is doing a profit.Sales growth is good if not followed by the implementation of a good managerial system will be a constraint on the percentage of Profit to be earned. A 24% increase in sales in 2013 and a 14.5% increase in Revenue are not followed by achieving a target percentage of target Bugget attainments such as COGS, Gross Profit and Store Expenses. These elements are a reflection of the level of performance management that can be measured by a percentage that greatly affects the SOI acquisition rate. The higher Percentage of Margin obtained allows the higher SOI level we get. Evaluation is needed to reconcile the ongoing strategy to obtain the relevance between corporate mission and managerial aspects at the operational level.Redefining Alternative Strategies as a result of the SWOT matrix analysis is an effective option for reducing operational issues and constraints related to existing business aspects such as customer satisfaction, operations, finance and human resources.